Nanoformulations of Essential Oils Extracted from Pistacia Lentiscus and Boswellia Sacra and Investigation of their Anticancer, Antimicrobial, and Antioxidant Activities. - Alabrahim, Obaydah Abd Alkader (AUC Knowledge Fountain, 2023)
Essential oils (EOs) obtained from natural sources have shown promising biological and therapeutical properties such as anticancer, antimicrobial, and antioxidant activities, attributing to their high content of a variety of bioactive components. However, EOs’ therapeutic properties are limited by their low stability, poor bioavailability, high volatility, and low targeting ability. Therefore, the encapsulation and nanoformulation of EOs can maximize their therapeutical efficiency and physicochemical properties while overcoming their undesirable side effects and drawbacks. EOs extracted from the resins of Pistacia Lentiscus var. Chia (P.oil) and Boswellia Sacra (B.oil) are two promising EOs that have shown great therapeutic potential. P.oil was successfully extracted, via a green extraction method of hydrodistillation, and its chemical composition was determined using GC-MS analysis technique. Thereafter, P.oil and 5-Fluorouracil (5FU), a chemotherapeutic agent, were loaded into poly-ε-caprolactone (PCL) nanofibers (PCL-NFs), via electrospinning technique, to compare and investigate their in-vitro anticancer activities and their potential synergistic properties against three cancer cell lines, two of them for breast cancer (MDA-MB-231 and MCF-7) and one for melanoma skin cancer (A375). The diameter size and morphology of the obtained NFs were determined using Field-emission scanning electron microscopy (FE-SEM), where all NFs groups showed an average diameter size between 300 and 600 nm. The encapsulation of P.oil and 5FU into NFs was further investigated using X-ray diffraction (XRD) and Fourier transform infrared (FT-IR) characterization techniques. The thermal stability of the NFs groups was examined using thermogravimetric analysis (TGA) technique to eventually show a greater stability among all NFs and an enhancement of the 5FU thermal stability by at least 1-fold. Also, NFs revealed excellent physical integrity over 70 days, showing good mechanical and physical properties while remaining intact without any dissolution or disintegration observed in their structures. Furthermore, the biodegradability study which was performed for 42 days showed great stability and prolonged degradation rates of all NFs with only ~5% weight loss observed by the end of the study, supporting the prolonged and biodegradable purposes of the NFs for local therapeutic use. Moreover, the in-vitro release studies of P.oil and 5FU revealed sustainable and prolonged release behaviors for 72h, without initial burst release. Also, higher released amounts of 5FU and P.oil were recorded in acidic media at pH 5.4 (phosphate buffer saline) compared to the physiological media (pH 7.4), which indicated the higher targeting ability of the loaded NFs. The NFs’ antioxidant activity was examined, using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay, and revealed great antioxidant properties of the NFs loaded with P.oil reaching 54.45% free-radicals scavenging. Finally, an MTT assay could be utilized to investigate the cytotoxic activity of free P.oil, free 5FU, PCL-NFs, 5FU loaded NFs (5FU-PCL-NFs), P.oil loaded NFs (P.oil-PCL-NFs), and the combination of P.oil and 5FU loaded NFs (5FU-P.oil-PCL-NFs) against MCF-7, MDA-MB231, and A375 cancer cell lines. For MCF-7 cancer cell line, P.oil-PCL-NFs showed a half-maximal inhibitory concentration (IC50) of 12.10 μg/mL compared to 67.31 μg/mL for free P.oil, and 5FU-PCL-NFs revealed an IC50 of 5.88 μg/mL compared to 7.87 μg/mL for free 5FU, whereas 5FU-P.oil-PCL-NFs showed higher cytotoxic activity with an IC50 of 3.82 μg/mL. Furthermore, for MDA-MB-231 cancer cells, P.oil-PCL-NFs showed an IC50 of 17.49 μg/mL compared to 93.58 μg/mL for free P.oil, and 5FU-PCL-NFs revealed an IC50 of 9.3 μg/mL compared to 16.14 μg/mL for free 5FU, whereas 5FU-P.oil-PCL-NFs showed higher cytotoxic activity with an IC50 of 5.28 μg/mL. Nevertheless, in case of A375 cancer cell line, P.oil-PCL-NFs showed an IC50 of 15.32 μg/mL compared to 73.21 μg/mL for free P.oil, and 5FU-PCL-NFs revealed an IC50 of 7.01 μg/mL compared to 12.32 μg/mL for free 5FU, whereas 5FU-P.oil-PCL-NFs showed higher cytotoxic activity with an IC50 of 4.24 μg/mL. Hence, NFs loaded with P.oil and 5FU depicted greater anticancer activity in comparison to their corresponding free compounds, and even higher anticancer activity could be observed with their combined NFs. On the other hand, B.oil and P.oil were encapsulated inside (2-Hydroxypropyl)-beta-cyclodextrins (HPβCD) via freeze-drying. The obtained inclusion complexes (ICs) of B.oil and P.oil showed remarkable entrapment efficiency (%EE) with 96.79 ± 1.17% and 89.59 ± 1.47%, respectively. Polydispersity index (PDI) and average size (Z-average) of B.oil-ICs were determined using Zetasizer with 0.1045 ± 0.0006 and 448.6 ± 0.6244 nm, respectively. PDI and Z-average of P.oil-ICs were also recorded with 0.1475 ± 0.0005 and 368.5 ± 0.5507 nm, respectively. Furthermore, the encapsulation of both EOs was investigated via FE-SEM, differential scanning calorimetry (DSC), proton nuclear magnetic resonance (1H NMR), and FT-IR. DSC could also reveal higher thermal stability of the ICs obtained. Finally, the ICs revealed a substantial increase in their antibacterial activities compared to their free EOs against Escherichia coli (E. coli), Pseudomonas aeruginosa (P. aeruginosa), and Staphylococcus aureus (S. aureus) bacteria.